Comparison of the Effectiveness of Cognitive-Behavioral Group Therapy Combined with Mindful Self-Compassion With and Without Physiotherapy on Executive Functions of Older Adults with Chronic Osteoarthritis-Related Pain - Shahabizadeh , Fatemeh; Faramarzi , Mahbobeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to compare the effectiveness of cognitive-behavioral group therapy combined with mindful self-compassion with and without physiotherapy on executive functions in older adults suffering from chronic osteoarthritis-related pain.Methods and Materials: Using a semi-experimental design with pre-test, post-test, and two-month follow-up, 45 older adults with chronic knee osteoarthritis pain were randomly assigned to one of three groups: (1) CBT combined with mindful self-compassion plus physiotherapy, (2) CBT combined with mindful self-compassion without physiotherapy, and (3) a control group. The intervention protocol consisted of 16 sessions over eight weeks for the psychological components, while the physiotherapy component included eight weekly sessions of ultrasound therapy. Executive functions were assessed using the Barkley Deficits in Executive Functioning Scale. Data were analyzed using ANCOVA and Bonferroni post-hoc tests.Findings: Results revealed a significant main effect of treatment on reducing executive function deficits after controlling for pre-test scores (F(2,41)=98.37, p